The intention of the young Muslim generation to purchase halal cosmetics: Do religiosity and halal knowledge matter? - Widjiarti Nur Riswandi; Sudarsono, Heri; Asri Noer Rahmi; Ali Hamza (Asian Journal of Islamic Management (AJIM), 2022)
Purpose – This study aims to examine the role of religiosity and knowledge in influencing subjective attitudes and norms. Then the influence of religion, knowledge, brand image, and product quality on the intention to buy Halal cosmetics products in the cosmetics industry in Indonesia.Methodology – This study used a purposive sampling method to collect data. As many as 522 young Muslim consumers in 32 provinces in Indonesia have previously used halal cosmetic products.Findings – The study results show that religiosity and Halal product knowledge significantly influence attitudes, subjective norms, and intentions to buy halal cosmetic products. Interestingly, the findings reveal that product knowledge has a higher impact on religiosity on attitudes, subjective norms, and intentions to buy in terms of cosmetics. Meanwhile, attitudes, brand image, and product quality affect intention, but subjective norms do not affect the intention of the young Muslim generation to buy cosmetic products.Implications – Halal cosmetic companies need to increase promotion to the younger generation of Muslims to introduce halal cosmetic products. This promotion will increase the knowledge of the young Muslim generation about halal cosmetics to increase the intention of the young Muslim generation to buy halal cosmetic products.Originality – Research develops the influence of knowledge and religiosity on attitudes and intention, and subjective norms to buy halal cosmetic products. The object of this research is the young Muslim generation, aged between 15 and 30 years, with mostly high school and university education.